2020
DOI: 10.3389/fcell.2020.605972
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2-Induced Neurological Complications

Abstract: Our review aims to highlight the neurological complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the available treatments according to the existing literature, discussing the underlying mechanisms. Since the end of 2019, SARS-CoV-2 has induced a worldwide pandemic that has threatened numerous lives. Fever, dry cough, and respiratory symptoms are typical manifestations of COVID-19. Recently, several neurological complications of the central and peripheral nervous systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 118 publications
1
11
0
Order By: Relevance
“…(15) Regarding disturbed sleep in Post COVID-19 subjects it was reported that many post COVID-19 recovered subjects complained of disturbed sleep which was consistent with the findings of this study. (16) Few mild manifestations reported by participants in the study could be related to hydroxychloroquine administration like effect on vision on few subjects, receiving this drug during their course of treatment. (17) The WHO estimated the median time from commencement of disease of COVID-19 till the period of healing is about 6 weeks founded by primary data from study in China.…”
Section: Discussionmentioning
confidence: 82%
“…(15) Regarding disturbed sleep in Post COVID-19 subjects it was reported that many post COVID-19 recovered subjects complained of disturbed sleep which was consistent with the findings of this study. (16) Few mild manifestations reported by participants in the study could be related to hydroxychloroquine administration like effect on vision on few subjects, receiving this drug during their course of treatment. (17) The WHO estimated the median time from commencement of disease of COVID-19 till the period of healing is about 6 weeks founded by primary data from study in China.…”
Section: Discussionmentioning
confidence: 82%
“…Phenytoin is helpful in only a minority of patients, it has also been related to exacerbated myoclonus seizures, and it only has value in the treatment of cortical myoclonus with motor seizures (palatal myoclonus) [ 30 ]. In addition to myoclonus, COVID-19 has been demonstrated to cause cerebral edema by the direct invasion of SARS-CoV-2 to the central nervous system (CNS) [ 31 ]. No case with simultaneous edema and myoclonus has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review evaluated nearly 300 COVID-19 patients found that 91% of patients who experienced some kind of a neurological complaint presented with CNS symptoms with headaches and dizziness being the commonest ones [ 140 ]. The most common CNS complication of COVID-19 was encephalopathy, which developed in about 50% of hospitalized patients mainly due to hypoxia or systemic disease [ 141 ].…”
Section: Vaccination Overview In the Context Of Multiple Sclerosismentioning
confidence: 99%
“…Some cases demonstrated oligoclonal bands or upregulated proteins levels in CSF analysis; however, others showed negative CSF findings. Treatments such as IVIG, steroids and plasma exchange brought clinical and radiological improvement and variating degrees of symptom relief [ 141 , 145 , 148 , 149 , 150 , 151 ].…”
Section: Vaccination Overview In the Context Of Multiple Sclerosismentioning
confidence: 99%